Bacterial communities along parrot digestive and respiratory tracts: the effects of sample type, species and time - Schmiedová, Lucie; Černá, Kateřina; Li, Tao; Těšický, Martin; Kreisinger, Jakub; Vinkler, Michal (International microbiology, 2024)
Digestive and respiratory tracts are inhabited by rich bacterial communities that can vary between their different segments. In comparison with other bird taxa with developed caeca, parrots that lack caeca have relatively lower variability in intestinal morphology. Here, based on 16S rRNA metabarcoding, we describe variation in microbiota across different parts of parrot digestive and respiratory tracts both at interspecies and intraspecies levels. In domesticated budgerigar (Melopsittacus undulatus), we describe the bacterial variation across eight selected sections of respiratory and digestive tracts, and three non-destructively collected sample types (faeces, and cloacal and oral swabs). Our results show important microbiota divergence between the upper and lower digestive tract, but similarities between respiratory tract and crop, and also between different intestinal segments. Faecal samples appear to provide a better proxy for intestinal microbiota composition than the cloacal swabs. Oral swabs had a similar bacterial composition as the crop and trachea. For a subset of tissues, we confirmed the same pattern also in six different parrot species. Finally, using the faeces and oral swabs in budgerigars, we revealed high oral, but low faecal microbiota stability during a 3-week period mimicking pre-experiment acclimation. Our findings provide a basis essential for microbiota-related experimental planning and result generalisation in non-poultry birds.
Keywords: Gastrointestinal tract microbiota; mikrobiota; Respiratory System; Psittaciformes; Symbiosis; dýchací soustava; RNA, Ribosomal, 16S; RNA ribozomální 16S; Bacteria; Animals; Microbiota; Budgerigar; Domestic parakeet; Microbiome composition; zvířata; papouškovití; Parrots